Determination of Microbial Count in Drinking Water Samples From Various Areas Of Dehradun, Uttarakhand - Sumira Malik, Aatish Raj, Prachi Priyanka (International Journal of Advanced Science and Technology, 2020)
The current study aims to determine and evaluate the quality and quantity of microbes in the drinking water samples collected from various locations of Dehradun city. This data determines and highlights the hygienic and sanitation practices of the population residing in different locations. The preliminary method of spread plate count and serial dilution technique showed the presence of coliforms which indicates the requirement in following of hygienic practices at various location of Dehradun. The microbial count also indicated presence of fungi (mold and yeast), spore formers with Salmonella gallinarum and Pseudomonas aeruginosa pathogens in localities. The samples of water collected from vasant vihar consist of contained highest number of spore former, 2.91X108±0.122 CFU/mL, whereas the samples from clement town showed highest load of mean viable count of 4.0X104±0.267 CFU/mL. The bacterial load showed a common ranging from 4.0X104±0.267 to 1.2X105±0.140 CFU/ml. The coliforms were reported in 60 % areas of the detected samples from ten regions of Dehradun. The presence of Salmonella gallinarum and Pseudomonas aeruginosa pathogens has been reported in the water samples of Jakhan, Naugaon, Patthri Bagh, Prem Nagar and colonies of Shimla bypass road of Dehradun. The results conclude there is a absence of good hygienic practices and awareness among inhabitants of these colonies and quality of water could be improved through the inclusion of awareness among the public regarding the importance of water treatment in their societies.